2023
DOI: 10.4194/trjfas22423
|View full text |Cite
|
Sign up to set email alerts
|

A New Model for Organic Contamination Assessments Using Benthic Macroinvertebrates as Biological Indicators

Abstract: The main goal of this study was to develop a model for organic pollution assessment. Seven sampling sites in six rivers in the Rawang sub-basin, Selangor River, Malaysia, were selected with one reference site. The sampling sites near the fish farm were used to develop the model. SR2 was used for the validation of the developed model. Benthic macroinvertebrates and water sampling were conducted from April 2019 to March 2020. The Principal Components Analysis (PCA) and regression were conducted to select the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Organic farming systems can be more resilient to climate change and contribute to overall health ecosystems, making them a critical component of sustainable agriculture. However, on the other hand, organic farming can also cause organic pollution in the surrounding area (Hettige et al, 2023), which will threaten the ecological state of the environment. It is also equally important to consider the qualitative composition of the soil and fertilizers applied during organic farming to minimize the negative impact on the general ecological state of the environment (Arynov et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Organic farming systems can be more resilient to climate change and contribute to overall health ecosystems, making them a critical component of sustainable agriculture. However, on the other hand, organic farming can also cause organic pollution in the surrounding area (Hettige et al, 2023), which will threaten the ecological state of the environment. It is also equally important to consider the qualitative composition of the soil and fertilizers applied during organic farming to minimize the negative impact on the general ecological state of the environment (Arynov et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The number of organisms is also affected by fluctuations in the physical and chemical characteristics of aquatic environments, such as water conditions, substrate composition, and currents (Odountan et al 2019). An instance of the basic substrate's condition, characterized by muddy sand and a high amount of organic substrate, leads to a diminished presence of benthic macroinvertebrate (Hettige et al 2023). In the context of aquatic ecosystems, it has been observed that the river riffle characterized by substantial rock and gravel substrates exhibits the most pronounced abundance and productivity of macroinvertebrate species.…”
Section: Aspt Valuementioning
confidence: 99%